2020
DOI: 10.1007/s41062-020-0274-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of elevated temperatures on the properties of mortar produced with volcanic ash

Abstract: During the recent years, the use of pozzolanic materials (e.g. volcanic ash) in concrete and cement manufacturing has increased significantly since it can reduce the environment hazard associated with using Portland cement. In this paper, the effect of elevated temperatures on the physical and mechanical characteristics of building mortar produced with volcanic ash is experimentally explored. In order to evaluate the performance of the mortar, four different proportions of volcanic ash (0, 5, 15 and 25%)-as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 28 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…A comparison of current experimental data with the results of linear regression by Awal and Shehu for control concrete [62] and power regression by Saha et al [58] is presented in Figure 11. Although, Awal and Shehu proposed different linear regressions (for control and palm oil fuel ash concretes) according to the exposure of 100 mm cube specimens up to 800 • C, their proposed regression for control concrete only reasonably predicts the residual strength of concrete for high exposure temperatures between 600 and 800 • C, while it underestimates the residual strength for exposure between 200 and 600 • C. The possible reason for this underestimated RCS can be due to the different geometry of their tested specimens (cubes), different heating regimes (exposure to peak temperature for 1 h only), and concrete of relatively lower strength (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) as compared to the current study (68-73 MPa). The power regression proposed by Saha et al was based on exposure of cylindrical specimens (100 mm × 200 mm) of ferronickel and FA concrete up to 800 • C. However, unlike Awal and Shehu, their prediction equation overestimated residual strength of concrete.…”
Section: Relationship Between Residual Compressive Strength and Upvmentioning
confidence: 96%
See 1 more Smart Citation
“…A comparison of current experimental data with the results of linear regression by Awal and Shehu for control concrete [62] and power regression by Saha et al [58] is presented in Figure 11. Although, Awal and Shehu proposed different linear regressions (for control and palm oil fuel ash concretes) according to the exposure of 100 mm cube specimens up to 800 • C, their proposed regression for control concrete only reasonably predicts the residual strength of concrete for high exposure temperatures between 600 and 800 • C, while it underestimates the residual strength for exposure between 200 and 600 • C. The possible reason for this underestimated RCS can be due to the different geometry of their tested specimens (cubes), different heating regimes (exposure to peak temperature for 1 h only), and concrete of relatively lower strength (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) as compared to the current study (68-73 MPa). The power regression proposed by Saha et al was based on exposure of cylindrical specimens (100 mm × 200 mm) of ferronickel and FA concrete up to 800 • C. However, unlike Awal and Shehu, their prediction equation overestimated residual strength of concrete.…”
Section: Relationship Between Residual Compressive Strength and Upvmentioning
confidence: 96%
“…Demirel and Kelestemur [27] exposed a concrete blended with a binary mixture of finely ground pumice (FGP) and SF to high temperatures. They concluded that the addition of both FGP and SF decreased the compressive strength and reduced the unit weight of concrete at a temperature above 600 • C. Mohamad et al [28] experimentally explored the performance of VA in cement mortar and they highlighted that the replacement of cement with VA affects the properties of mortar at a later age at both ambient and high temperatures. The addition of VA up to 20% in the HSC exhibited better resistance to chloride penetrability and deterioration along with an enhancement in the residual strength subjected to a high temperature of about 800 • C. However, reduced durability and loss of strength were noticeable when the temperature increased beyond 800 • C [29].…”
Section: Introductionmentioning
confidence: 99%
“…Single consolidation test was carried out using an oedometer cell and following the procedures indicated by Mohamed et al [23], and Jennings and Knight [24] to determine the collapse potential of the samples. The sample in this test is loaded in a dry state without any water according to the standard consolidation test.…”
Section: Collapsibility Characteristics (Consolidation Test)mentioning
confidence: 99%
“…Three different temperature ranges are generally used in concrete studies that include low temperature (<0 • C), medium temperature (0-50 • C), and high or elevated temperature (<50 • C). The thermal response of concrete to elevated temperature mainly depends on constituents' characteristics and the mix composition [38]. Based on the applications and intended exposure condition, previous researches have considered various temperature ranges to evaluate the thermal response of concrete which can be classified as temperatures below 200 • C [39][40][41], below 600 • C [42][43][44], and below 1000 • C [45][46][47].…”
mentioning
confidence: 99%